Optimal Foreign Exchange Market Intervention: Evidence from the Bretton Woods Era - Jones, Michael (The Review of Economics and Statistics, 1984)
Abstrac-t-This paper gathers evidence on the contribution of various techniques of exchange rate management to the output stability of twelve industrial countries. We estimate the distribution of unanticipated disturbances in outputs and the payments balances under pegged exchange rates from the 1955-1971 experience. We use this distribution to characterize the foreign exchange market intervention procedures which simultaneously minimize the output variances of the sample countries. The efficient procedures and the alternatives of managed floats, basket pegs, and the European currency area are compared according to structure and efficacy; and several implications for I.M.F. surveillance of exchange rates are drawn.